Dinamika dan Tantangan Kelembagaan Ekonomi Islam: Studi Komparatif antara Arab Saudi dan Rusia - Fauzan Fauzan; Naufal Luthfi Alifa (INAIFAS Press, 2026)
This study examines the dynamics, challenges, and comparative aspects of Islamic economic institutions in Saudi Arabia and Russia by exploring differences in geography, demography, regulatory frameworks, and institutional capacity. Using a literature review method, the research synthesizes empirical findings from international studies published over the past five years. The results indicate that Saudi Arabia possesses a more developed Islamic economic institutional ecosystem due to centralized regulation, strong social legitimacy, and the integration of Islamic finance within national development strategies. Conversely, Russia faces structural barriers, including the absence of federal regulation for Islamic finance, uneven bureaucratic capacity, and low public literacy regarding Islamic financial services. These findings highlight that regulatory quality, social legitimacy, and institutional coordination are key determinants of successful Islamic economic institutionalization. The study contributes to comparative Islamic economics literature and provides direction for developing adaptive institutional models suitable for various national contexts.